Endangered man: A view of the Christian scholar* - Dekker, J. (Koers, 1978)
The seventies will most probably go down in history as one of the most critical periods in the history of mankind. Simultaneously with the petroleum crisis of 1973 man has become intensely conscious of his dependence on irreplaceable natural resources. It is, therefore, not to be wondered at that existentialism with its emphasis on the present and its lack of hope for the future has become so viable a world view in our time. Man, who cannot or will not perceive the hand of God within Creation, is a confused being who wants to evade the future because of the threat it poses to him.